Comparison of preoperative urinary Titin levels and serum Titin levels in patients with gastrointestinal malignancy - Shimoda, Mitsugi; Izumi, Kihiro; Shiihara, Masahiro; Watanabe, Mitsuru; Miyamoto, Ryoichi; Shimazaki, Jiro; Suzuki, Shuji (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Background: In recent years, reports using urinary Titin (U-Titin) levels to evaluate patients with muscular dystrophy, myocardial infarction, myasthenia gravis, gastrointestinal malignancy (GIM), chronic liver disease, and sarcopenia have been sporadically observed; however, reports using serum Titin (S-Titin) levels are scarce. We report here on the measurement of S-Titin, which has now become feasible.Methods: This study included 104 patients who underwent surgery for the diagnosis of GIM in our department between May 2024 and November 2025. Preoperative S-Titin and U-Titin levels were measured to investigate their correlation. Furthermore, using InBody, we measured skeletal muscle mass index (SMI), percent body fat (PBF), fat mass index (FMI), extracellular water (ECW)/total body water (TBW) and whole-body phase angle (Ph A) to investigate the relationship with S-Titin and U-Titin.Results: There were 28 female and 76 male patients, with a median age of 68 (range, 54–89) years. Location of malignant diseases was as follows: 42 cases of hepatobiliary-pancreatic cancer, 36 cases of colorectal cancer, and 26 cases of upper gastrointestinal cancer. S-Titin and U-Titin levels showed a strong positive correlation (r=0.78, y=0.19x+1.40, P